(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
Contamination of soil with heavy metals is one of the types of contamination of farm field soil with toxic elements as a result of mineral feeding of plants used in agriculture and the use of many pesticides similar to hexachlorocyclohexane used in the former Soviet era has been found to be similar. The highest amount was found in the soil taken from the area of the old agricultural airfield depot, the amount of copper was 1580 mg/kg, which is 526 times the permissible amount, and molybdenum was 639 mg/kg, which was 63.9 times the permissible amount.